High-Intensity Exercise Mitigates Cardiovascular Deconditioning During Long-Duration Bed Rest - Maggioni, Martina A.; Castiglioni, Paolo; Merati, Giampiero; Brauns, Katharina; Gunga, Hanns-Christian; Mendt, Stefan; Opatz, Oliver S.; Rundfeldt, Lea C.; Steinach, Mathias; Werner, Anika; Stahn, Alexander C. (Frontiers in Physiology, 2018)
Head-down-tilt bed rest (HDT) mimics the changes in hemodynamics and autonomic cardiovascular control induced by weightlessness. However, the time course and reciprocal interplay of these adaptations, and the effective exercise protocol as a countermeasure need further clarification. The overarching aim of this work (as part of a European Space Agency sponsored long-term bed rest study) was therefore to evaluate the time course of cardiovascular hemodynamics and autonomic control during prolonged HDT and to assess whether short-duration/high-intensity exercise could mitigate these effects. A total of n=23 healthy, young, male participants were randomly allocated to two groups: training (TRAIN, n=12) and non-training (CTRL, n=11) before undergoing a 60-day HDT. The TRAIN group underwent a resistance training protocol using reactive jumps (5-6 times per week), whereas the CTRL group did not perform countermeasures. Finger blood pressure (BP), heart rate (HR), and stroke volume were collected beat-by-beat for 10 minutes in both sitting and supine positions 7 days before HDT (BDC-7) and 10 days after HDT (R+10), as well as on the 2nd (HDT2), 28th (HDT28), and 56th (HDT56) day of HDT. We investigated 1) the isolated effects of long-term HDT by comparing all the supine positions (including BDC-7 and R+10 at 0 degrees), and 2) the reactivity of the autonomic response before and after long-term HDT using a specific postural stimulus (i.e. supine vs. sitting). Two-factorial linear mixed models were used to assess the time course of HDT and the effect of the countermeasure. Starting from HDT28 onwards, HR increased (p<0.02) and parasympathetic tone decreased exclusively in the CTRL group (p<0.0001). Moreover, after 60-day HDT, CTRL participants showed significant impairments in increasing cardiac sympathovagal balance and controlling BP levels during postural shift (supine to sitting), whereas TRAIN participants did not. Results show that a 10-day recovery did not compensate for the cardiovascular and autonomic deconditioning following 60-day HDT. This has to be considered when designing rehabilitation programs – not only for astronauts but also in general public healthcare. High-intensity, short-duration exercise training effectively minimized these impairments and should therefore deserve consideration as a cardiovascular deconditioning countermeasure for spaceflight.